Some results on the Krein parameters of an association scheme - Mano, Vasco Moço (2016)
We consider association schemes with d classes and the underlying Bose- Mesner algebra, A. Then, by taking into account the relationship between the Hadamard and the Kronecker products of matrices and making use of some matrix techniques over the idempotents of the unique basis of minimal orthogonal idempotents of A , we prove some results over the Krein parameters of an association scheme.